Quality of life among liver transplantation patients - Y. Sirivatanauksorn (2018)
Background: Orthotopic liver transplantation (OLT) is the treatment of choice for end-stage disease. It offers a chance to return to an active and prolonged life. Recently, more attention is being paid to the health-related quality of life (HRQoL) of patients and their spouses or caregivers after OLT. The aim of this study was to analyze the pre- versus posttransplantation HRQoL of patients and their spouses or caregivers using generic and disease-specific health questionnaires. Material and Methods: The study was performed between October 2010 and January 2011 using the Short Form-36 (SF-36) and the Chronic Liver Disease Questionnaire (CLDQ) to evaluate the HRQoL. Results: Posttransplantation patients (N = 59, mean age 53.39 [range, 23 to 76] years, male 63.2%, female 36.8%) and their spouses and caregivers showed significantly better generic SF-36 HRQoL scores, namely, physical and social functioning, role limitations because of physical or emotional problems, bodily pain, vitality, as well as general and mental health compared with pretransplantation patients (N = 57, mean age 54.56 (range, 22 to 69) years, male 71.2%, female 28.8%). Similarly, the posttransplantation group showed significantly improved CLDQ scores in all domains: fatigue, activity, abdominal symptoms, systemic symptoms, emotional function, and worry. Conclusion: OLT improved HRQoL of end-stage liver patients and their spouses or caregivers. © 2012 by Elsevier Inc. All rights reserved.